Transformation of Electronic-Based Licensing Services in Realizing Investment Certainty: An Economic Law Analysis - Anne Nurjanah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The transformation of electronic-based licensing services is one of the government's strategies in creating a conducive investment climate through increasing legal certainty, bureaucratic efficiency, and transparency of public services. The implementation of the digital licensing system not only functions as an administrative instrument of government, but is also an important part of the development of economic laws that support ease of doing business and protection for investment actors. This study aims to analyze the transformation of electronic-based licensing services through the Integrated Licensing Service Information System (SIPPADU) in realizing investment certainty based on the perspective of economic law. The research uses an analytical descriptive method with a normative juridical approach supported by empirical data through interviews, literature studies, analysis of laws and regulations, and official documents. The results of the study show that the implementation of SIPPADU has increased the efficiency of the licensing process, strengthened transparency, accelerated services, and reduced maladministration practices that have the potential to hinder investment activities. From an economic law perspective, the system contributes to strengthening legal certainty, increasing investor confidence, and supporting the creation of a more competitive business climate. However, the effectiveness of implementation still faces obstacles in the form of limited digital infrastructure, human resource competence, inter-agency system integration, and low digital literacy among some people. Therefore, it is necessary to strengthen regulations, increase the capacity of apparatus, optimize information technology, and harmonize licensing policies so that the transformation of electronic-based services is able to provide a guarantee of investment certainty in a sustainable manner and encourage national economic growth.